Bridging Gaps: Cross-Sector Collaboration in Improving Sanitation Access in Last-Miles Communities of South Sulawesi, Indonesia - Muh. Saleh; Wildan Setiabudi; Andi Bunga Tongeng; Hamsah Sinring; Nildawati Nildawati; Ain Khaer; Muhammad Rachmat (Journal of Public Health and Pharmacy, 2026)
ntroduction: According to the Global Burden of Disease study, approximately 775,000 lives were lost prematurely in 2017 due to poor sanitation. In 2020, only 54% of the global population had access to safely managed sanitation. Therefore, this study aimed to explore cross-sector collaboration for improving sanitation access at "last mile" communities in South Sulawesi, Indonesia. Barriers to achieving Open Defecation Free (ODF) status were emphasized, with a focus on the dynamics between health centers (puskesmas) and village governments. Methods: This qualitative case study was conducted with key stakeholders who were directly engaged in the STBM program, such as managers, district government officers, health officers, as well as sub-district, village, and puskesmas heads. Focus group discussions (FGDs) and in-depth interviews were used to collect data. Analysis was conducted thematically to determine patterns and obstacles to collaboration. Results: There was no synergy between puskesmas and village governments in enhancing access to sanitation. Puskesmas operated by modifying the behavior of communities to construct their own latrines, while the village governments operated by providing financial support through village funds. This isolation led to community reliance on outside assistance as well as lowered ODF program effectiveness. FGDs also showed misconceptions among the stakeholders, and external influences on the pathogen spread to water and food sources (e.g., vectors (e.g., flies) spreading pathogens). Conclusion: The synergy between puskesmas and village governments was a critical obstacle to attaining the ideal level of sanitation access and ODF status in the last-mile communities. Enhancing partnership by considering integrated planning, better communication, and participation of the community is necessary. The study showed that the existence of vectors, such as flies, worsened the sanitation issues. This underscores the significance of integrated and sustainable cross-sector partnerships to enhance access to sanitation and control vectors.